Faktor-faktor yang Mempengaruhi Praktik Perataan Laba pada Perusahaan - perusahaan di Bursa Efek Jakarta - Antariksa Budileksmana; Eka Andriani (Universitas Muhammadiyah Yogyakarta, Indonesia, 2005)
A recent analysis held that there is a significantly effect between firm size, corporate risk, profitability and operating leverage to corporate income smoothing practices. The objective of this research is to empirically re-examine the factors could affect income smoothing practices.There are four factors will be examined, are firm size, corporate risk, profitability and operating leverage. The sample used in this study are 76 firms listed at Jakarta Stock Exchange (JSX) over 2000 to 2002. The multivariate test which using logistic regression results both risk and profitability affect significantly to income smoothing practices. While firm size and operating leverage not affect significantly to income smoothing practices. The univariate test support the previous test, shows that there is statistically difference in risk as well as profitability between smoother and non-smoother firms. Whereas both firm size and operating leverage, there are no statistically difference.